Inclusion compounds of a borneol dumb-bell host with methylcyclohexanones and 2-butanols: structures and resolutions1. Issue 22 (14th June 2015) - Batisai, Eustina; Nassimbeni, Luigi R.; Weber, Edwin
<x xml:space="preserve">Abstract</x> Partial resolution of racemic methylcyclohexanones and 2-butanol via inclusion within a borneol dumb-bell host.